2010
DOI: 10.1007/s10811-010-9545-3
|View full text |Cite
|
Sign up to set email alerts
|

Hybridity of carrageenans water- and alkali-extracted from Chondracanthus chamissoi, Mazzaella laminarioides, Sarcothalia crispata, and Sarcothalia radula

Abstract: Carrageenans water-and alkali-extracted from Chondracanthus chamissoi, Mazzaella laminarioides, Sarcothalia crispata, and Sarcothalia radula were degraded by Pseudoalteromonas carrageenovora κ-carrageenase and Alteromonas fortis ι-carrageenase. The composition of the high molecular weight fraction (i.e., enzyme-resistant fraction) as well as the standard and hybrid oligosaccharide content highlighted differences between the species-specific carrageenans in terms of composition and distribution of the carrabios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…Altogether, the results obtained in this study confirmed the presence of κ/μ-and ι/ν-carrageenan structures in the aqueous extracts from cystocarpic and vegetative M. laminarioides and are in accordance to those published by Jouanneau et al (2011) for unsorted commercial samples of M. laminarioides.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Altogether, the results obtained in this study confirmed the presence of κ/μ-and ι/ν-carrageenan structures in the aqueous extracts from cystocarpic and vegetative M. laminarioides and are in accordance to those published by Jouanneau et al (2011) for unsorted commercial samples of M. laminarioides.…”
Section: Discussionsupporting
confidence: 90%
“…The first study on the characterization of sulfated galactans from unsorted Iridaea laminarioides collected in central Chilean coast (32°5 8′ 00″ S, 71°29′ 00″ W) was performed in 1976; fractionation of the aqueous extract using increasing concentration of KCl showed the presence of a mixture of sulfated galactans (Matsuhiro and Zanlungo 1976). More recently, Jouanneau et al (2011) conducted the enzymatic degradation of phycocolloids from commercial unsorted samples of Chilean M. laminarioides; they reported the presence of κ-and ι-carrageenan, and their precursors μ-and ν-carrageenan in the same galactan chain indicating the hybrid nature of the carrageenan systems. M. laminarioides grows abundantly in the Magellan Ecoregion, southernmost Chile, and it is not exploited for industrial purposes .…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the experimental data with a statistical block copolymer model suggested the existence of randomly distributed blocks of at least 8 to 14 G4S-DA diads and 2 to 5 G4S-DA2S diads, depending on the experimental technique used to probe the transitions and the type of salt used to induce the helical formation and aggregation. The lengths of the blocks are overall of the same order of the lengths actually inferred from the enzymatic degradation studies [30,32]. But more importantly, the latter underlined that the distribution of block lengths along the K2 chain varies from chain to chain and that this compositional variation is specific to the seaweed producing the K2, as well as the extraction process.…”
Section: Statistical Block Copolymer Structure Of Gelling Hybrid Carr...supporting
confidence: 59%
“…Clearly, this topic deserves more research efforts. However, few studies avoid seaweeds drying and grinding to bypass any possible effect on extracted K2 characteristics, whereas larger K2 recovery yields are not needed [30,31,38]. Another process, the dark treatment of carrageenophytes during cultivation after harvesting, has also attracted little research, in contrast to the dark treatment of seaweeds used in the production of agar.…”
Section: Extraction Of Hybrid Carrageenansmentioning
confidence: 99%
See 1 more Smart Citation